PEMETAAN KATALOG KERUANGAN “RUANG BERSAMA INDONESIA”, KELURAHAN KENDRAN, BULELENG, BALI - Regina Suryadjaja; Suryono Herlambang (Jurnal Serina Abdimas, 2025)
Ruang Bersama Indonesia (RBI) is a new program initiated by the Ministry of Women's Empowerment and Child Protection (Kemen P3A) in January 2025 in Bali. Meanwhile, Kendran Village is one of 11 villages/villages that are the focus of the RBI program development. The RBI program is expected to be a friendly space for women, mothers and children so that there needs to be a minimum standard that is met regarding child-friendly spaces. Basically, RBI carries 24 basic indicators that have been initiated in the Child-Friendly Regency/City Program (KLA) in 2005. For this reason, this study conducted a mapping of the existing spatial catalog in Kendran Village which is seen from the physical space and socio-economic space. The methods used for mapping the RBI Spatial Catalog in Kendran Village are using drone mapping, field surveys, field observations, and interviews. The results obtained from the RBI Spatial Catalog mapping will be used by the next team as a basis for making RBI proposals in Kendran Village. ABSTRAK Ruang Bersama Indonesia (RBI) merupakan program baru yang diinisiasi oleh Kementerian Pemberdayaan Perempuan dan Perlindungan Anak (Kemen P3A) pada Januari 2025 di Bali. Adapun, Kelurahan Kendran menjadi salah satu dari 11 kelurahan/desa yang menjadi fokus pengembangan program RBI. Program RBI diharapkan dapat menjadi ruang yang ramah bagi Perempuan, ibu dan anak sehingga perlu ada standar minimal yang dipenuhi terkait ruang ramah anak. Pada dasarnya, RBI mengusung 24 indikator dasar yang telah dicanangkan di Program Kabupaten/Kota Layak Anak (KLA) pada tahun 2005. Untuk itu, studi ini melakukan pemetaan katalog keruangan eksisting di Kelurahan Kendran yang dilihat dari keruangan fisik dan keruangan social-ekonomi. Adapun metode yang digunakan untuk pemetaan Katalog Keruangan RBI di Kelurahan Kendran adalah menggunakan drone mapping, survei lapangan, observasi lapangan, dan wawancara. Hasil yang diperoleh dari pemetaan Katalog Keruangan RBI akan digunakan oleh tim selanjutnya sebagai dasar untuk membuat usulan RBI di Kelurahan Kendran ini.